FACTORS INFLUENCING THE PROFITABILITY OF SMES FROM THE REPUBLIC OF SERBIA: FOOD INDUSTRY - Novaković, Dragana; Milić, Dragan; Tomaš Simin, Mirela; Jocic, Bogdan; Novaković, Tihomir (Economics of Agriculture, 2025)
Drawing from an extensive literature review on the impact of microeconomic and macroeconomic variables on the profitability of food enterprises globally and within national markets, this research analyzes the performance of small and medium-sized food companies in the Republic of Serbia from 2014 to 2022. The objective of this paper is to analyze the influence of microeconomic and macroeconomic factors on their profitability. By applying panel regression analysis, the impact of various factors on profitability, measured by return on assets, was examined. The research findings indicate that both the current asset turnover ratio and the growth rate of gross domestic product exert a significant positive influence on the profitability of the examined enterprises, whereas factors such as indebtedness, average collection period, asset tangibility, and inflation demonstrate a significant negative impact.